p-type NiO hybrid visible photodetector - Mallows, John; Planells, Miguel; Thakare, Vishal; Bhosale, Reshma; Ogale, Satishchandra; Robertson, Neil (ACS Applied Materials & Interfaces, 2015)
A novel hybrid visible-light photodetector was created using a planar p-type inorganic NiO layer in a junction with an organic electron acceptor layer. The effect of different oxygen pressures on formation of the NiO layer by pulsed laser deposition shows that higher pressure increases the charge carrier density of the film and lowers the dark current in the device. The addition of a monolayer of small molecules containing conjugated pi systems and carboxyl groups at the device interface was also investigated and with correct alignment of the energy levels improves the device performance with respect to the quantum efficiency, responsivity, and photogeneration. The thickness of the Organic layer was also optimized for the device, giving a responsivity of 1.54 X 10(-2) A W-1 in 460 nm light.
Keywords: nickel oxide; organic; oxygen vacancies; photodetector; pulsed laser deposition; surface modifier

Chromium free high temperature water-gas shift catalyst for the production of hydrogen from waste derived synthesis gas - Jha, Ajay; Jeong, Dae-Woon; Lee, Yeol-Lim; Jang, Won-Jun; Shim, Jae-Oh; Jeon, Kyung-Won; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Applied Catalysis A-General, 2016)
A comparative study between monometallic (Me-CeO2, Me =Zn, Cu, Fe and Co) and Ni-doped bimetallic (Me-Ni-CeO2) catalysts has been performed in the high temperature water-gas shift (HT-WGS) reaction using waste derived synthesis gas. Experimental results revealed that Me-Ni-CeO2 exhibited higher catalytic performance than simple Me-CeO2 catalysts. Within the Me-Ni-CeO2 series, Co-Ni-CeO2 exhibited excellent and stable catalytic performance (CO conversion > 90%) at a very high GHSV of 143,000 h(-1). The existence of high" concentration of Ce3+ ions and oxygen vacancies on the catalyst surface were responsible for the increased WGS activity of Co-Ni-CeO2. In addition, Co-Ni-CeO2 maintains a stable performance for 50 h. However, commercial Fe2O3-Cr2O3 catalyst showed a steep decline from their initial CO conversion values 15-10% within 5 h. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: CeO2; Co-Ni-CeO2; Lattice strain; oxygen vacancies; Water-gas shift

Direct oxidation of cyclohexane to adipic acid by a WFeCoO(OH) catalyst: role of bronsted acidity and oxygen vacancies - Vernekar, Dnyanesh; Dayyan, Mohammad; Ratha, Satyajit; Rode, V, Chandrashekhar; Haider, M. Ali; Khan, Tuhin Suvra; Jagadeesan, Dinesh (ACS Catalysis, 2021)
This work reports the catalytic activity of the trimetallic mixed-metal oxyhydroxide WFeCoO(OH) for the direct oxidation of cyclohexane to adipic acid (AA) without the use of concentrated HNO3. WFeCoO(OH) displayed a 40% conversion of cyclohexane and a 67% selectivity to AA under relatively milder conditions of temperature (90 degrees C) and pressure (1 atm). Experimental evidence confirmed the presence of acidic, basic, and redox sites on WFeCoO(OH). The detailed investigation revealed that doping W in the Co-FeO(OH) matrix increased the amount of surface lattice oxygen (OS-L) and caused a significant surge in acidity (5.1 mmol/g). The calculated deprotonation energy of WFeCoO(OH) was 1434 kJ/mol, and the trend in acidity was WCoO(OH) < WFeCoO(OH) < FeCoO(OH) similar to CoO(OH). Energy calculations showed that WFeCoO(OH) had a high propensity to generate oxygen vacancies by the loss of either a water molecule or an oxygen atom (-132.2 or -140.9 kJ/mol, respectively). Basicity was generated due to the presence of conjugate pairs of the surface hydroxyl groups. The combined action of the trifunctional acidic, basic, and redox-active metal centers along with the oxygen vacancies was responsible for the enhanced catalytic performance.
Keywords: Adipic Acid; deprotonation energy; metal oxyhydroxides; multifunctional catalysts; oxygen vacancies

Role of metal-support interaction for atmospheric pressure CO2 hydrogenation over Pd/(Ti)-SBA-15 catalyst: effect of titanium composition on products selectivity - Soni, Yogita; Gupta, Sharad; Vinod, C. P. (Molecular Catalysis, 2021)
The potential role of metal-support interaction for tuning the product selectivity during atmospheric pressure CO2 hydrogenation has been demonstrated on Pd/(Ti)-SBA-15 catalyst. Highly dispersed Pd NPs on SBA-15 (Pd/ SBA-15) was synthesized and further modified with titanium of varying composition. Comparison of catalytic activity of Pd/Ti-SBA-15 with its counterparts (Pd/SBA-15 and Pd/TiO2) illustrated the significance of strong PdTi interface in this catalyst and its role in tuning the product selectivity of CO2 hydrogenation. The generation of an ample amount of oxygen vacancies in the Pd/Ti-SBA-15 catalyst with maximum metallic Pd sites in close vicinity of Ti is proposed to boost the CO2 hydrogenation activity.
Keywords: CO2 hydrogenation; Metal-support interaction; Modified deposition precipitation; oxygen vacancies; Titanosilicates

Phenol hydrogenation to cyclohexanol catalysed by palladium supported on CuO/CeO2 - Kasabe, Mirabai M.; Kotkar, Vaibhav R.; Dongare, Mohan K.; Umbarkar, Shubhangi B. (Chemistry-an asian jounrnal, 2023)
Hydrogenation of phenol to cyclohexanone/cyclohexanol is an important reaction in production of nylon-6, nylon-66 and in petroleum industry. Liquid phase phenol hydrogenation over Pd-CuO/CeO2 was carried out under mild conditions. Palladium impregnated over CuO/CeO2 synthesized by co-precipitation method showed excellent catalytic activity for phenol hydrogenation (99% conversion with 80% cyclohexanol yield) at 90 degrees C and 10 bar H-2 pressure in water. Commercial 10%Pd/C showed only 8% phenol conversion under identical conditions. The detailed characterization revealed significant improvement in surface area of ceria after addition of CuO and decrease in crystallite size with creation of defects in CeO2 lattice. XPS analysis showed Pd loading on CuO/CeO2 to cause hydrogen spillover on the surface leading to increase in the oxygen vacancies. The interaction of phenol with catalyst surface studied by detailed FTIR analysis, revealed activation of phenol on oxygen vacancy of ceria as phenoxide ion with perpendicular orientation of aromatic ring on catalyst surface.
Keywords: Cyclohexanol; Hydrogen spillover; oxygen vacancies; Pd-CuO/CeO2; phenol hydrogenation